Pendampingan Bimbingan Qur’ani untuk Meningkatkan Kesadaran dan Cinta Lingkungan Hidup Bersih di Wilayah RW. 5 Desa Sibanteng Bogor - Ahmad Waki; Ikhsan Maulana (Reslaj: Religion Education Social Laa Roiba Journal, 2025)
This Community Service Program aims to enhance awareness and love for a clean environment through Qur’anic guidance assistance in RW. 5, Sibanteng Village, Leuwi Sadeng District, Bogor. The method used is Participatory Action Research (PAR) with approaches including Mapping, Transect Walk, Matrix Ranking, Timeline, and Trend and Change. The results show that public awareness of environmental cleanliness remains low, as indicated by the habit of dumping waste into rivers and the lack of waste management facilities. Through weekly Qur’anic study sessions, the community has begun to show positive behavioral changes regarding the importance of cleanliness as part of religious practice. This program provides tangible contributions in fostering a clean and environmentally friendly culture within religious communities.